Elucidation of secondary alcohol metabolism in Starmerella bombicola and contribution of primary alcohol oxidase FAO1. Issue 2 (11th February 2019) - Takahashi, Fumikazu; Igarashi, Kazuaki; Takimura, Yasushi; Yamamoto, Takashi
ABSTRACT: The yeast Starmerella bombicola NBRC10243 is an excellent producer of sophorolipids, which are among the most useful biosurfactants. The primary alcoholic metabolic pathway of S. bombicola has been elucidated using alcohol oxidase FAO1, but the secondary alcohol metabolic pathway remains unknown. Although the FAO1 mutant was unable to grow with secondary alcohols and seemed to be involved in the secondary alcohol metabolism pathway of S. bombicola, it had very low activity toward secondary alcohols. By analyzing the products of secondary alcohol metabolism, alkyl polyglucosides hydroxylated at the ω position in the alkyl chain of the secondary alcohol were observed in the FAO1 mutant, but not in the wild-type yeast. In the double mutant of FAO1 and UGTA1, accumulation of 1, 13-tetradecandiol and 2, 13-tetradecandiol was observed. The above results indicated that hydroxylation occurred first at the ω and ω–1 positions in the secondary alcohol metabolism of S. bombicola, followed by primary alcohol oxidation. Abstract : We clarified the long-chain secondary alcohol utilization pathway in glycolipid producing yeast Starmerella bombicola and clarified the contribution of FAO1, which is a primary alcohol oxidase.